(untitled) (Journal of Pathology of Nepal, 2016)
Primary tracheal tumors are rare. Adenoid cystic carcinoma of trachea is even rarer. It occurs as a polypoidal mass in trachea presenting with dyspnea and respiratory distress due to tracheobronchial obstruction. We report a case of young male presenting with dyspnea for some time. CT scan revealed mass in trachea obliterating its lumen. Histopathological examination conirmed the diagnosis.